The outcome of patients with stage I endometrial cancer involving the lower uterine segment. Issue 5 (1st August 2008) - Lavie, O.; Uriev, L.; Gdalevich, M.; Barak, F.; Peer, G.; Auslender, R.; Anteby, E.; Gemer, O.
Abstract : The objective of this study was to evaluate whether lower uterine segment involvement (LUSI) correlates with recurrence and survival in women with stage I endometrial adenocarcinoma and whether it is associated with poor prognostic histopathologic features. Three hundred seventy-five consecutive patients with endometrial carcinoma stage I compromised the study population. The patients were divided into two groups according to the presence of LUSI with endometrial carcinoma. The two groups were compared with regard to prognostic factors and outcome measures by using the Pearson χ 2 test, log-rank test, and Cox proportional hazards model. LUSI was present in 89 (24%) patients with stage I endometrial carcinoma. LUSI was significantly associated with grade 3 tumor ( P = 0.022), deep myometrial invasion ( P < 0.0001), and the presence of capillary space-like involvement (CSLI) ( P = 0.003). Kaplan–Meier survival curves demonstrated that patients with LUSI had a lower recurrence-free survival (log-rank test; P = 0.009) and a worse overall survival (log-rank test; P = 0.0008). In the Cox proportional hazards model, only a trend toward higher recurrence rate (HR = 2.4, 95% CI 0.7, 8.2; P = 0.16) and a trend toward poorer overall survival (HR = 1.54, 95% CI 0.82, 2.91; P = 0.18) were noted when LUSI was present. In patients with stage I endometrial cancer, the presence of LUSI is associated with grade 3 tumor, deep myometrial invasion, and the presence of CSLI. A larger group of patients is necessary to conclude whether higher recurrence rate and poorer overall survival are associated with the presence of LUSI.